Fibronectin is up-regulated in podocytes by mechanical stress - Kliewe, Felix; Kaling, Sören; Lötzsch, Henriette; Artelt, Nadine; Schindler, Maximilian; Rogge, Henrik; Schröder, Sindy; Scharf, Christian; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; et al. (The FASEB Journal, 2019)
Hypertension is one of the central causes of kidney damage. In the past it was shown that glomerular hypertension leads to morphologic changes of podocytes and effacement and is responsible for detachment of these postmitotic cells. Because we have shown that podocytes are mechanosensitive and respond to mechanical stress by reorganization of the actin cytoskeleton in vitro, we look for mechanotransducers in podocytes. In this study, we demonstrate that the extracellular matrix protein fibronectin (Fn1) might be a potential candidate. The present study shows that Fn1 is essential for the attachment of podocytes during mechanical stress. By real-time quantitative PCR as well as by liquid chromatography-mass spectrometry, we found a significant up-regulation of Fn1 caused by mechanical stretch (3 d, 0.5 Hz, and 5% extension). To study the role of Fn1 in cultured podocytes under mechanical stress, Fn1 was knocked down (Fn1 KD) by a specific small interfering RNA. Additionally, we established a Fn1 knockout (KO) podocyte cell line (Fn1 KO) by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). During mechanical stress, a significant loss of podocytes (>80%) was observed in Fn1 KD as well as Fn1 KO podocytes compared with control cells. Furthermore, Fn1 KO podocytes showed a significant down-regulation of the focal adhesion proteins talin, vinculin, and paxillin and a reduced cell spreading, indicating an important role of Fn1 in adhesion. Analyses of kidney sections from patients with diabetic nephropathy have shown a significant up-regulation of FN1 in contrast to control biopsies. In summary, we show that Fn1 plays an important role in the adaptation of podocytes to mechanical stress.-Kliewe, F., Kaling, S., Lötzsch, H., Artelt, N., Schindler, M., Rogge, H., Schröder, S., Scharf, C., Amann, K., Daniel, C., Lindenmeyer, M. T., Cohen, C. D., Endlich, K., Endlich, N. Fibronectin is up-regulated in podocytes by mechanical stress.
EVALuna2:204845
Keywords: Fn1; extracellular matrix; hypertension; mechanical load; diabetic nephropathy